1990
DOI: 10.1002/1097-0142(19900415)65:8<1820::aid-cncr2820650826>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Tissue carcinoembryonic antigen and dna aneuploidy in precancerous and cancerous colorectal lesions

Abstract: Chronic inflammatory bowel disease (CIBD) and colorectal adenoma are considered as precancerous conditions and lesions of large bowel carcinoma, respectively. They, therefore, may be used to study the behavior of such different factors as tumor-associated antigens and nuclear DNA content abnormalities in colorectal carcinogenesis. Tissue concentrations of carcinoembryonic antigen (CEA) were significantly higher in those precancerous lesions (CIBD: 61 k 11.2 ng/mg, adenoma: 70 2 6 ng/mg; mean ? standard error o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 33 publications
0
7
1
Order By: Relevance
“…The relationship between them, however, is still not settled. Some studies have demonstrated a significant association between the two markers (Hammarberg et al, 1984;Melville et al, 1988), whereas in other reports, no relationship was found Fischbach et al, 1990). In the present study, we could demonstrate no significant association between DNA ploidy pattern and dysplasia.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The relationship between them, however, is still not settled. Some studies have demonstrated a significant association between the two markers (Hammarberg et al, 1984;Melville et al, 1988), whereas in other reports, no relationship was found Fischbach et al, 1990). In the present study, we could demonstrate no significant association between DNA ploidy pattern and dysplasia.…”
Section: Discussioncontrasting
confidence: 75%
“…Aneuploid cell populations have previously been found by DNA flow cytometry in the colonic mucosa of patients with ulcerative colitis, both preceding and coexistent with colonic carcinomas. Diverging results have been reported, however, both with regard to the proportion of aneuploid carcinomas in patients with ulcerative colitis, as well as the relationship between dysplasia and aneuploidy in tumour-distant flat mucosa (Hammarberg et al, 1984, L0fberg et al, 1987, Melville et al, 1988, Fischbach et al, 1990). …”
mentioning
confidence: 99%
“…As an example, intestinal bowel disease is an autoimmune disease that is characterized by a non-limited inflammation in the gut and elevated CEA expression in the inflammatory lesion. 16,17 Due to the chronic inflammatory process, intestinal bowel disease is thought to be a precancerosis with the therapeutic need to repress the ongoing inflammatory process. The latter is currently aimed to be achieved by the systemic application of non-steroid antiphlogistic drugs, however, with remarkable systemic site effects.…”
Section: Discussionmentioning
confidence: 99%
“…Ulcerative Colitis Multiple reports have shown that DNA aneuploidy may be found in dysplastic epithelium in ulcerative colitis (UC) and DNA aneuploidy may often precede cancer in UC (45)(46)(47)(48)(49). It has therefore been suggested that FCM may help to identify the UC patients who are in greatest need of surveillance endoscopy.…”
Section: Future Directionsmentioning
confidence: 99%